GAYA BAHASA KOMUNIKASI DAKWAH DALAM CERAMAH SYEKH SULAIMAN BIN SALIMULLAH AR RUHAILY - Lia Fatra Nurlaela; Endry Boeriswati; Shafruddin Tajuddin (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
The purpose of this research is to broaden the understanding of the study of language analysis used in da'wah communication, to provide an overview and knowledge of forms of da'wah communication language that can be applied in everyday life and can be used as an example of qualitative research, especially content analysis. This study uses a content analysis method with a qualitative approach. The data collection technique is done by content analysis. The results showed that the form of da'wah communication style in terms of the End aspect in the lectures delivered by Syekh Sulaiman bin Salimullah Ar Ruhaily found as many as 26 utterances. The form of da'wah communication style in terms of the Act Sequences aspect was found to be 44 utterances. The form of da'wah communication style in terms of genre aspects was found as many as 29 utterances